2021
DOI: 10.1021/acssuschemeng.0c08340
|View full text |Cite
|
Sign up to set email alerts
|

Construction of Lanthanum Vanadate/Functionalized Boron Nitride Nanocomposite: The Electrochemical Sensor for Monitoring of Furazolidone

Abstract: The electrochemical sensor has received considerable attention because of the future on-time monitoring technologies. To meet the requirements of on-time monitoring applications, it is of prodigious importance to discover new catalysts for the electrochemical sensor that have good conductivity and physicochemical properties. The novelty of this work is the successful synthesis of lanthanum vanadate/functionalized boron nitride (LaV/F-BN) nanocomposites and their application toward the electrochemical detection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
47
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 75 publications
(48 citation statements)
references
References 68 publications
1
47
0
Order By: Relevance
“…36 The stacking of the 2D nanomaterials with other heterostructures capacitates the inherent limitations of primary constituents in terms of structural instability and generates appreciable changes in the electronic structures rendering increased charge transport and conformal contact. 37 In this work we thus report, based on Kokulnathan et al, 27 LaV incorporated with h-BN in a different approach based on Liu et al 38 reported a biocompatible deep eutectic synthesis method for preparation of RE metal vanadate. The as-prepared efficient LaV/h-BN electrocatalyst applied for electrochemical determination of CZ.…”
Section: ■ Introductionmentioning
confidence: 86%
See 2 more Smart Citations
“…36 The stacking of the 2D nanomaterials with other heterostructures capacitates the inherent limitations of primary constituents in terms of structural instability and generates appreciable changes in the electronic structures rendering increased charge transport and conformal contact. 37 In this work we thus report, based on Kokulnathan et al, 27 LaV incorporated with h-BN in a different approach based on Liu et al 38 reported a biocompatible deep eutectic synthesis method for preparation of RE metal vanadate. The as-prepared efficient LaV/h-BN electrocatalyst applied for electrochemical determination of CZ.…”
Section: ■ Introductionmentioning
confidence: 86%
“…In this work we thus report, based on Kokulnathan et al, LaV incorporated with h-BN in a different approach based on Liu et al reported a biocompatible deep eutectic synthesis method for preparation of RE metal vanadate. The as-prepared efficient LaV/h-BN electrocatalyst applied for electrochemical determination of CZ.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…In addition, hexagonal boron nitride nanosheets (HBNNS) are called “white graphene” due to the isostructural similarity to graphene. At the same time, due to the excellent electronic properties, superior catalytic activity, mechanical properties, outstanding biocompatibility and excellent chemical stability, HBNNS have attracted significant interest in electrochemical applications, such as sensors [17–21] . Hence, it is expected that the HBNNS combined with carbon‐based materials can improve the electrochemical properties of the traditional solid electrodes [22–24] .…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, due to the excellent electronic properties, superior catalytic activity, mechanical properties, outstanding biocompatibility and excellent chemical stability, HBNNS have attracted significant interest in electrochemical applications, such as sensors. [17][18][19][20][21] Hence, it is expected that the HBNNS combined with carbon-based materials can improve the electrochemical properties of the traditional solid electrodes. [22][23][24] For example, an electrochemical sensor based on 2D-hBN/f-MWCNTs nanocomposite was constructed for the simultaneous detection of β-agonists.…”
Section: Introductionmentioning
confidence: 99%